1987
DOI: 10.1007/bf00377579
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis in epiphytic and rooted Clusia rosea Jacq.

Abstract: Clusia rosea Jacq. is a hemiepiphyte having Crassulacean Acid Metabolism (CAM). In its natural habitat Clusia begins its life cycle as an epiphyte and eventually becomes a rooted tree. These two stages of the life cycle of Clusia represent markedly different water regimes. Our CO exchange, stomatal conductance, titratable acidity, and stable carbon isotope ratio measurements indicate that Clusia has a flexible photosynthetic mode, where CO is fixed mostly via CAM during its epiphytic stage, when water availabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
3

Year Published

1987
1987
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 9 publications
0
13
3
Order By: Relevance
“…The carbon isotope ratios found in our material are somewhat different from those presented by Ting et al (1985) and Sternberg et al (1987) for C. rosea. In the plants they studied in southern Florida, CAM was more pronounced in the dry season compared to the rainy season and in the juvenile epiphtytic stage compared to rooted trees.…”
Section: E a F Anatomycontrasting
confidence: 75%
See 3 more Smart Citations
“…The carbon isotope ratios found in our material are somewhat different from those presented by Ting et al (1985) and Sternberg et al (1987) for C. rosea. In the plants they studied in southern Florida, CAM was more pronounced in the dry season compared to the rainy season and in the juvenile epiphtytic stage compared to rooted trees.…”
Section: E a F Anatomycontrasting
confidence: 75%
“…In contrast, the values of the present investigation, where only rooted trees were studied, range up to -14.7%0 for C. rosea and up to -14.1%0 for C. alata, showing that in adult and rooted trees (see Fig. 2a-c) CAM is just as strongly expressed as in the epiphytic specimens analysed by Sternberg et al (1987). The latter authors also suggested that there might be differences between leaves of different age.…”
Section: E a F Anatomycontrasting
confidence: 70%
See 2 more Smart Citations
“…This serves firstly Ojanguren & Vasquez-Yanes (1983). Studies in the for a better understanding of the life stages and life field (Ting et al, 1985Popp et al, 1987; forms of C rosea, and secondly, as a basis for the Sternberg et al,, 1987) and in the laboratory investigation of its modes of photosynthesis (Ball (Schmitt, Lee & Luttge, 1988;Lee, Schmitt & et al,, \99\), Luttge, 1989;Franco, Ball & Luttge, 1990) (clusia with respect to both diversity of life forms and mode of photosynthesis. Chemical analyses were performed either from leaf sap or from rapidly oven-dried material.…”
mentioning
confidence: 99%